Teaching strategies for self-care of the intestinal stoma patients - Janaína da Silva; Helena Megumi Sonobe; Luciana Scatralhe Buetto; Marco Gimenes dos Santos; Mariza Silva de Lima; Vanessa Damiana Menis Sasaki (Rev Rene)
Teaching self-care must ensure the intestinal stoma patient more independence concerning the family and health professionals. The planning involves the assessment of the clinical and socio-demographic data, and the conditions for the self-care. This study aimed at identifying strategies to teach self-care for intestinal stoma patients in the scientific production. We used an integrative review on MEDLINE, PUBMED, LILACS, CINAHL and COCHRANE bases from 2005 to 2011, 7 papers were selected. In the perioperative teaching, multimedia, telephone follow-up, personal meetings, interactive material through the Internet were used, besides the continuing education of the health professionals. These different strategies profess the needs of each individual that promote self-care learning about the surgery and its consequences, skills development and the necessary adaptation of the condition of a stoma patient. The nurse needs to have technical and scientific knowledge on surgical technique, demarcation, treatment, complications, and skills for the teaching of self-care.